Efeito do pré-tratamento com l-alanil glutamina e precondicionamento isquêmico em modelo de isquemia : reperfusão de membros pélvicos em ratos - Landim, Emanuel Rocha (2008)
The present work determined the effects of pre-treatment with L-alanyl glutamine (Ala-Gln) and ischemic preconditioning (IPC), alone and in combination, against lesions caused by I/R by clamping the infrarenal aorta in rats. Sixty Wistar rats were distributed into five groups (n = 12) divided into two times (n = 6): Control, Group I/R, Group IPC + I/R, Group Ala-Gln + I/R, Group Ala-Gln + IPC + I/R. Times: T1 (infrarenal-aorta clamping ischemia-4h); T2 (ischemia-4h plus reperfusion-1h). Pulmonary myeloperoxidase (MPO) and plasma TBARS concentrations were measured. Data expressed as mean ± standard-deviation, analyzed by Student’s t-test and ANOVA/Tukey’s post-test. P-values < 0,05 were considered significant. Increased MPO concentrations in ischemic group and in I/R group occurred as compared to control. Reduction in MPO concentrations happened in ischemic groups pre-treated with either Ala-Gln or IPC. I/R induced no change in MPO concentrations in groups pre-treated with either Ala-Gln or IPC. Pre-treating with the two procedures showed increased MPO at both times studied. Reduction in TBARS concentrations occurred in Ala-Gln pre-treated group, whereas significant elevation was observed when Ala-Gln and IPC were associated in ischemic animals. Ischemia/reperfusion induced elevation of plasma TBARS. Pre-treatment with either Ala-Gln or IPC protects against distant pulmonary lesion due to ischemia. The same did not occur in I/R lesion. Combining the two procedures aggravated inflammation indicated by increased MPO concentrations. Elevated TBARS concentrations in ischemic animals pre-treated with the two procedures indicate increased lipid peroxidation, whereas pre-treatment with Ala-Gln induced decreased TBARS concentrations.